Konsep Desain Rurung Sebagai Ruang Terbuka Multifungsi Studi Kasus: Koridor Jalan Karna, Kelurahan Ubud, Gianyar, Bali - Krispariyana, Cokorda Alit; Semarajaya, Cokorda Gede Alit; Sukewijaya, I Made (Jurnal Arsitektur Lansekap; Vol. 10, No. 1 April 2024DO - 10.24843/JAL.2024.v10.i01.p06, 2024)
The Jalan Karna Ubud Corridor is classified as an environmental road that is commonly known as a means of connecting the community with the surrounding space. Along with its development, the road corridor underwent many changes, which caused the comfort and function of this road corridor to be reduced. The purpose of this study is to produce a rurung design concept that can accommodate community activities as a multifunctional facility in the community environment, as well as describe the phenomenon of the rurung space as a multifunctional space. The research method used is a survey method with the data collection process using observation, questionnaires, interviews, and literature studies. The basic concept developed is space as a multifunctional space, namely the application of the concept of open space in order to facilitate various community activities carried out in that space. Thus, it is hoped that the presence of a road corridor as a multi-functional space in facilitating community activities will be able to provide a sense of balance with the balance of needs between users who have differences in each individual community. It is also hoped that the existence of this road corridor can become an icon or distinctive and, at the same time, can become a feature or example in other areas of Bali.